Implementation of STEAM Learning with Magic Puffer Ball for Children with Special Needs - Kumala, Hena Safira Endah; Mustakimah, Mustakimah; Irmanda, Novi Dina (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2023)
TK Talenta is an inclusion school in Semarang. TK Talenta accepts all children without differences in ethnicity, religion, socio-economy, even children with special needs can study at TK Talenta. STEAM learning is considered very effective to be applied to early childhood and TK Talenta also applies it in learning activities. This study aims to determine the implementation of STEAM learning with magic puffer ball games in TK Talenta. Descriptive qualitative research is the type and approach of research used in this study. Data from this study were obtained through observation, interviews, and documentation. Then the data that has been collected will be analyzed using qualitative descriptive analysis. The results of this study show that STEAM learning in TK Talenta is in accordance with the stages of implementing STEAM learning in early childhood. Children are given the freedom to express and imagine according to their wishes to create works. Even with the implementation of STEAM learning with magic puffer ball games at TK Talenta, children with special needs get a lot of sensory nutrition.